PERGESERAN FUNGSI MAMAK KANDUNG DALAM PELAKSANAAN ADAT MINANGKABAU PADA MASYARAKAT JORONG BATU BADINDING NAGARI LIMO KOTO KECAMATAN BONJOL KABUPATEN PASAMAN - Hafizah, Hafizah (Universitas Lancang Kuning, 2019)
This study aims to reveal the shifting forms of mother's brother function in the guardianship Batu Badinding community, the cause of the shift in the function of mother's brother biological in the customar practices of the Minangkabau people in the guardianship Batu Badinding community, the impact of the shift in the function of the mother's brother in the implementation of the Minangkabau Customs in guardianship Batu Badinding. This is a case study research. The informant selection technique uses a method (purposive sampling). the results showed that there had been a shift in the function of mother's brother biological in guardianship Batu Badinding community (1) The forms of shifting functions of mother's brother were: (a) in the economic field, (b) in the field of education, (c) in the religious field, and ( d) in the field of Custom (e) in the field of marriage. (2) The causes of the shifting of mother's brother biological functions are: (a) lifestyle in overseas, (b) mother's brother prioritizes children and wives, (c) lack of indigenous knowledge of mother's brother (d) low economic level of mother's brother , (e) mother's brother morality low, (f) the influence of values in Islam. (3) The impact of the shift in the function of the mother's brother biological, namely: (a) the mother's brother figure is less respected by the niece, (b) the authority of mother's brother begins to fade in the middle of the community (c) the fading of kinship and social relations between mother's brother and niece, (d) changes in structure and responsibility family answer.